Smartphone-based identification of dangerous driving situations: Algorithms and implementation - Alexander Smirnov (Proceedings of the XXth Conference of Open Innovations Association FRUCT, 2016)

(untitled)
In this paper, we demonstrate the concept of the situation analysis of dangerous driving events for smartphones to fully understand the driving situation in a given scenario in a real time and to undertake actions necessary to avoid road accidents. To fulfil these, we utilize a wide array of sensors for creating a consistent and extendable description of most common dangerous situations, a situation model and situation analysis. In the situation model, on-board smartphone sensing signals are used to build up a representation of the environment around and within the vehicle. On top of the situation model, a situation analysis is established to detect driver hazards, according to the given description of the driving situation, and provide a driving strategy to prevent such dangerous situations. The paper describes the details of the algorithms, following by simulation results, which show the feasibility of the proposed algorithm.